PERENCANAAN DAN ANALISIS BIAYA PEMELIHARAAN (MAINTENANCE COST) ARMADA BUS TRANSJAKARTA RK260 CNG PADA PERUSAHAAN DISTRIBUTOR KENDARAAN KOMERSIAL: Indonesia, Inggris - Dhimas Derra Adipratama; Zainal Arifin (Journal of Automotive Technology and Education, 2025)
Abstract This study aims to identify the processes and aspects used to obtain accurate results in planning maintenance costs for vehicles using the On-site Service scheme for Transjakarta RK260 CNG buses. The type of research used is quantitative descriptive research with the object of research being the planning of maintenance costs for the Transjakarta RK260 CNG bus fleet. This research was conducted by collecting primary data from direct observations in the field and secondary data from sources related to the research topic. The results of this research testing obtained aspects used in the vehicle maintenance cost budget planning process, namely analysis of the operational key performance index (KPI) requirements of the unit, operational information of the unit, identification of spare part requirements, identification of equipment requirements, labour, and finally calculating the vehicle maintenance cost design. The results of the calculation using the cost per kilometre (CPK) method showed that the total maintenance cost budget for the 2023 period was Rp 2.694 per kilometre. The total planned vehicle maintenance cost budget was Rp 10,159,980,826 for the fifth year of the vehicle's life. Keywords: Bus Rapid Transit; Vehicle Maintenance Costs; On-site Service; Cost per Kilometre Abstrak Penelitian ini bertujuan untuk mengidentifikasi proses dan aspek-aspek yang digunakan untuk mendapatkan hasil akurat dalam perencanaan anggaran biaya perawatan kendaraan dengan skema On-site Service pada unit bus Transjakarta RK260 CNG. Jenis penelitian yang digunakan yakni penelitian deskriptif kuantitatif dengan objek penelitiannya adalah perencanaan anggaran biaya perawatan kendaraan untuk armada bus Transjakarta RK260 CNG. Penelitian ini dilakukan dengan mengumpulkan data primer yang berasal dari hasil observasi langsung di lapangan penelitian dan data sekunder diambil dari data yang memiliki hubungan dengan topik penelitian. Hasil dari pengujian penelitian ini didapatkan aspek-aspek yang digunakan dalam proses perencanaan anggaran biaya perawatan kendaraan yaitu Analisa kebutuhan key performance index (KPI) operasional unit, informasi operasional unit, identifikasi kebutuhan spare part, identifikasi kebutuhan peralatan, tenaga kerja, dan diakhiri menghitung rancangan biaya perawatan kendaraan. Hasil dari perhitungan dengan metode cost per kilometer (CPK) didapat total anggaran biaya perawatan periode tahun 2023 sebesar Rp. 2.694, - per kilometer. Total perencanaan anggaran biaya perawatan kendaraan adalah sebesar Rp. 10.159.980.826, - untuk periode tahun ke lima umur kendaraan. Kata kunci: Bus Rapid Transit; Biaya Perawatan Kendaraan; On-site Service; Cost per Kilometer